Social construction of the environment and smallholder farmers' participation in 'low-carbon', agro-industrial crop production contracts in the Philippines - Montefrio, Marvin Joseph F. (Animo Repository, 2015)
Several studies have suggested that socio-economic factors and production site characteristics are primary determinants of farmers' participation in 'low-carbon', agro-industrial (biofuels and oil palm) production contracts. In the Philippines, many smallholder farmers have expressed their intent to participate in intensive production of biofuel crops and oil palm with state and private organizations; others have resisted or remained indifferent. This study looks into smallholders' social construction of the environment and how this may influence their decisions to participate in such production contracts. The study is based on a survey of 462 respondents in eight communities in the province of Palawan. Using regression analysis, it illustrates how smallholders' sense of place and environmental worldviews, together with demographic and socio-economic variables, play significant roles in their decisions to enter into new biofuels (jatropha) and oil palm production contracts. Environmental worldviews are significant when there are strong negative perceptions attached to a particular crop production contract, as in the case of oil palm. © 2015 Elsevier B.V.